2021
DOI: 10.1177/09645284211009543
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators of and barriers to implementing a traditional Chinese medicine collaborative model of care for axial spondyloarthritis: a qualitative study

Abstract: Background: Conventional therapy may be inadequate for many patients with axial spondyloarthritis (axSpA). Traditional Chinese medicine (TCM) may be a viable alternative, but its effectiveness for axSpA is unknown. We are currently conducting a pragmatic randomised controlled trial (RCT) to investigate the effectiveness of a TCM collaborative model of care (TCMCMC), which combines usual rheumatologic care with acupuncture for patients with axSpA. This nested qualitative sub-study aims to identify facilitators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 16 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…These studies confirmed perceived efficacy and highlighted the value of education, exercise and nonpharmacological therapy in general, when used alongside pharmacological interventions. [71][72][73][74][75][76][77][78] It is already well-established that csDMARDs are ineffective in treating axial symptoms in patients with in axSpA, 106,107 a finding once again observed in this SLR. It is also already known that comedication with csDMARDs can reduce immunogenicity against bDMARDs.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…These studies confirmed perceived efficacy and highlighted the value of education, exercise and nonpharmacological therapy in general, when used alongside pharmacological interventions. [71][72][73][74][75][76][77][78] It is already well-established that csDMARDs are ineffective in treating axial symptoms in patients with in axSpA, 106,107 a finding once again observed in this SLR. It is also already known that comedication with csDMARDs can reduce immunogenicity against bDMARDs.…”
Section: Discussionmentioning
confidence: 61%
“…cognitive–behavioural therapy). These studies confirmed perceived efficacy and highlighted the value of education, exercise and non-pharmacological therapy in general, when used alongside pharmacological interventions 71–78…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations